Raman micro-spectroscopy monitors acquired resistance to targeted cancer therapy at the cellular level. Issue 1 (December 2018) - Hammoud, Mohamad; Yosef, Hesham; Lechtonen, Tatjana; Aljakouch, Karim; Schuler, Martin; Alsaidi, Wissam; Daho, Ibrahim; Maghnouj, Abdelouahid; Hahn, Stephan; El-Mashtoly, Samir; Gerwert, Klaus
Abstract Monitoring the drug efficacy or resistancein vitro is usually carried out by measuring the response of single few proteins. However, observation of single proteins instead of an integral cell response may lead to results that are not consistent with patient's response to a drug. We present a Raman spectroscopic method that detects the integral cell response to drugs such as tyrosine kinase inhibitors (TKIs). Non-small cell lung cancer (NSCLC) patients with EGFR mutations develop acquired resistance to first (erlotinib)- and third (osimertinib)-generation TKIs. Large erlotinib-induced differences were detected by Raman micro-spectroscopy in NSCLC cells without T790M EGFR mutation but not in cells with this mutation. Additionally, Raman difference spectra detected the response of NSCLC cells with T790M EGFR mutation to second- (neratinib) and third-generation (osimertinib) TKIs, and the resistance of cells with T790M/C797S EGFR mutation to osimertinib. Thus, thein vitro Raman results indicated that NSCLC cells with T790M and T790M/C797S EGFR mutations are resistant to erlotinib- and osimertinib, respectively, consistent with the observed responses of patients. This study shows the potential of Raman micro-spectroscopy to monitor drug resistance and opens a new door toin vitro companion diagnostics for screening personalized therapies.